WHEN THE INFLUENCE OF BRAND LOVE ON BUYING SATISFACTION AND INTENTION - Fariz, Nur; Kustiawan, Unggul (Jurnal Ilmu Manajemen (JIMMU), 2023)
This study seeks to examine the influence of brand love formed by brand experience and brand trust on e-satisfaction and see the possibility of customers to return to using online services, especially in the field of food products. This survey were selected using purposive sampling in Jabota (an acronym of Jakarta – Bogor – Tangerang) with the sampling criteria of this study is online food delivery customers, was conducted in October - November 2020 with interviews using questionnairesusers, using a survey with online questionnaires. Data analysis used factor analysis and Lisrel-structural equation modeling (SEM). The findings of this study are hypotheses that support, among others, brand experience contributes to brand love, then brand love shows positive results that affect e-satisfaction, and brand love also has a positive effect with re-purchase intentions. This resaurce interpreted while brand trust does not have a positive effect on brand love, brand experience does not show positive results on re-purchase intention and e-satisfaction also does not contribute positively to re-purchase intention. This study interprets the brand factors that influence e-purchase intentions as influenced by brand love, e satisfaction, brand experience and brand trust. This study seeks to explore whether they influence customers to be able to e-purchase.